Design and characterization of microfluidic analysis system for RNA-aminoglycoside interactions - Lee, JH; Jang, JM; Cho, HS; Han, KC; Kim, TS; Kang, JY; Yang, EG (TRANS TECH PUBLICATIONS LTD, 2005)
Microfluidic devices are of considerable interest, since such technology offers great promise for the development of powerful and versatile miniaturized analyzers. Accordingly, the present work describes a microfluidic screening system that is composed of a microchip, hydrodynamic pumping unit and fluorescence detectors. To develop an assay for RNA-aminoglycoside interactions, microchips are designed and fabricated on a glass substrate, then flow simulations are performed in the microchannels. After optimizing the flow control and buffer composition for fluorescence-based biochemical assays, a fluorescently labeled aminoglycoside probe and RNA are allowed to flow continuously to the main micro-channel based on hydrodynamic pumping and their interactions monitored by fluorescence quenching, which is reversed upon competition with other aminoglycosides. Consequently, the proposed device can serve as an integrated microfluidic platform for the high-throughput screening of high affinity antibiotics for RNA targets.